SOSIALISASI DAN PEMBENTUKAN PEER EDUCATOR REMAJA PUTRI SEBAGAI UPAYA MENANGGULANGI ANEMIA DI DESA SUNGAI TABUK KERAMAT - Solechah, Siti Aisyah; Rahmah, Zulfa Nur Haliza; Safitri, Eva Dwi; Qamra, Hasna Luthfiyyah; Rizky, Karin Carolina Amanda (Jurnal Abdi Insani, 2025)
Anemia is a serious health issue among adolescent girls, with one of the main causes being the low intake of iron supplements (Tablet Tambah Darah/TTD). In South Kalimantan, the prevalence of anemia in adolescent girls reaches 53.3%, yet TTD consumption coverage remains low. In Sungai Tabuk Keramat Village, 56.7% of adolescent girls had not received TTD in the past year. This community service program aimed to increase knowledge and compliance with TTD intake through the establishment of peer educators. Activities included health education, training on the use of hemoglobin (Hb) measuring devices, peer educator development, and 2.5 months of monitoring. The results showed that 92% of participants improved their knowledge of Hb device usage, and 92% of those re-tested achieved normal Hb levels. Monitoring of TTD consumption recorded that 31.6% of adolescents adhered to recommended intake in August, but this declined to 15.8% in September. This program proved effective in enhancing knowledge and hemoglobin levels among adolescent girls and demonstrated that peer educators can serve as effective educational agents. However, maintaining long-term adherence to TTD intake remains a challenge. Therefore, continuous support, increased involvement of families and health cadres, and strengthened monitoring systems are essential to sustain the program’s impact and contribute significantly to anemia prevention among adolescent girls.